Mengenal Obat secara Lebih Dekat bersama Anak-anak Panti Asuhan Manarul Mabrur - Nur Alifah Arbianti; Alfina Irawati; Arrofik Nurraji; Gloria Dwi Wulandari (jurnal ABDIMAS Indonesia, 2024)
Community service activity on "Getting to Know Medicine More Closely with the Children of the Manarul Mabrur Orphanage" located on Pudak Umbrella, Banyumanik, Semarang, Central Java. The aim of this community service activity is to spread knowledge and be able to improve the quality of life and daily behavior to the wider community, including the children of the orphanage. This education is provided using education methods to the children of the orphanage. The first is education about what forms of drug preparation there are and the second is education about how many categories of drugs there are and the third is education about the use/method of consuming drugs and storing drugs, then the next activity continues with questions and answers and a pretest was held before the presentation of the material and a posttest after the presentation of the material for all children at the orphanage.  Before the education, the level of knowledge was quite good, but after the presentation of the educational material, the level of knowledge was very good. In this case, students are able to understand the material that has been presented and increase the knowledge of the children of the orphanage.